Safe assets - Robert J. Barro; Jesús Fernández-Villaverde; Oren Levintal; Andrew Mollerus (American Enterprise Institute (AEI), 2017)
A safe asset's real value is insulated from shocks, including declines in GDP from rare macroeconomic disasters. However, in a Lucas-tree world, the aggregate risk is given by the process for GDP and cannot be altered by the creation of safe assets. Therefore, in the equilibrium of a representative-agent version of this economy, the quantity of safe assets will be nil. With heterogeneity in coefficients of relative risk aversion, safe assets can take the form of private bond issues from low-risk-aversion to high-risk-aversion agents. The model assumes Epstein-Zin/Weil preferences with common values of the intertemporal elasticity of substitution and the rate of time preference. The model achieves stationarity by allowing for random shifts in coefficients of relative risk aversion. We derive the equilibrium values of the ratio of safe to total assets, the shares of each agent in equity ownership and wealth, and the rates of return on safe and risky assets. In a baseline case, the steady-state risk-free rate is 1.0% per year, the unlevered equity premium is 4.2%, and the quantity of safe assets ranges up to 15% of economy-wide assets (comprising the capitalized value of GDP). A disaster shock leads to an extended period in which the share of wealth held by the low-risk-averse agent and the risk-free rate are low but rising, and the ratio of safe to total assets is high but falling. In the baseline model, Ricardian Equivalence holds in that added government bonds have no effect on rates of return and the net quantity of safe assets. Surprisingly, the crowding-out coefficient for private bonds with respect to public bonds is not 0 or -1 but around -0.5, a value found in some existing empirical studies.
Keywords: 330